Role of Radiation Based Conditioning Regimens in Patients With High-Risk AML Undergoing Allogenic Transplantation in Remission or Active Disease and Mechanisms of Post-Transplant Relapse - Salhotra, Amandeep; Stein, Anthony Selwyn (Frontiers in Oncology, 2022)
In the last decade there has been a consistent improvement in the clinical outcomes of patients diagnosed with acute leukemia undergoing allogenic stem cell transplantation. These improvements are due to more precise risk stratification of leukemia patients made possible by incorporation of molecular mutation testing at diagnosis, MRD assessment pretransplant and attempts to clear residual disease prior to transplant. Improvements in targeted therapies, immunotherapies, and availability of novel drug combinations with BCL-2 inhibitors has also improved remission rates for patients who are undergoing transplant. For patients who are unable to achieve a morphologic or MRD negative remission prior to transplant, the risk of relapse post-transplant remains high and for these patients’ intensification of conditioning regimen may be able to overcome risk of increased relapse rate. However, in the past increased nonrelapse mortality associated with escalation of conditioning intensity has neutralized any potential benefit of decreasing relapse rate in HCT patient resulting in no significant improvement in overall survival. In this review we discuss incorporation of newer techniques to deliver targeted doses of radiation at high doses using total marrow and lymphoid irradiation in order to improve outcomes of patients with active leukemia. We also discuss potential mechanisms associated with leukemia relapse despite use of intensified conditioning regimens.